TRIAL CRIME OF MURDER IN INDONESIAN CRIMINAL LAW (A PUNISHMENT PERSPECTIVE) - Akbar Rifqy Kautsar; M. Ya’kub Aiyub Kadir (Fakultas Hukum Universitas Syiah Kuala, 2021)
- Trial to commit a criminal act can be interpreted as an act intended to realize what is categorized by law as a criminal act, but the act does not succeed in realizing the original plan to be achieved. It has already begun, but it is not finished. The purpose of this thesis is to investigate the criminal act of trial crime of murder in the (KUHP), and the judge's consideration in imposing a sentence for trial crime of murder in Indonesia, as also called a punishment perspective. The study finds that the sentence for a person who commits the crime of trial crime of murder has a one-third reduction of the sentence in the main criminal offense. The judges' considerations the object of the research were in the form of intention, initiation of implementation, and incomplete actions due to reasons other than the perpetrator. This research uses normative legal research method. Normative legal research is process to find legal rules, legal principles, and doctrines of law. based on the KUHP namely Article 338 juncto articles 53, The judge should define in determining the length of the sentence imposed, as well as pay attention to the mental state and motive of the perpetrator to commit the act, so that there is no punishment disvarities.Keywords: Trial; Trial Crime; Murder; Trial Crime of Murder; KUHP Indonesia.